2021
DOI: 10.1103/physrevapplied.15.024037
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Processes in Magnetization Reversal Involving Domain-Wall Motion in Magnetic Memory Elements

Abstract: We show experimentally through single-shot time-resolved conductance measurements that magnetization reversal through domain wall motion in sub-100 nm diameter magnetic tunnel junctions is dominated by two distinct stochastic effects. The first involves the incubation delay related to domain wall nucleation, while the second results from stochastic motion in the Walker regime. Micromagnetics simulations reveal several contributions to temporal pinning of the wall near the disc center, including vertical Bloch … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…In this paper, we study part of this problem: we let aside the nucleation phenomenon and focus on the subsequent dynamics of a domain wall placed in a circular magnet and then submitted to STT. We expand a recent study [23] where we evidenced that stochastic processes in wall motion were inducing counterintuitive temporal pinning of the wall near the disc center with a strong oscillatory character. These features were also reported independently in a modeling paper [24].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…In this paper, we study part of this problem: we let aside the nucleation phenomenon and focus on the subsequent dynamics of a domain wall placed in a circular magnet and then submitted to STT. We expand a recent study [23] where we evidenced that stochastic processes in wall motion were inducing counterintuitive temporal pinning of the wall near the disc center with a strong oscillatory character. These features were also reported independently in a modeling paper [24].…”
Section: Introductionsupporting
confidence: 71%
“…33), the DEVice OptimaL DiametER (DE-VOLDER) for which the retention pond disappears. For this specific diameter, we predict that the wall shall cross the disc center in a ballistic manner independently of its tilt such that the time needed for a domain wall to sweep through the disc will get largely independent from its tilt [23]. This is expected to maximize the reproducibility of the wall dynamics, which is of great interest for magnetic memory applications.…”
Section: B Domain Wall Dynamics At Different Voltagesmentioning
confidence: 99%
See 1 more Smart Citation
“…A separate study of magnetization reversal on magnetic disks, based on the stochastic motion of a domain wall [73,74], uses the wall position and the wall's tilt (i.e., the in-plane orientation at the center wall) to analyze magnetization reversal. This work compares results from micromagnetic simulations at room temperature to key features of the deterministic, reduced-dimensional model, and is able to predict whether the reversal occurs with a single sweep of the domain wall, or whether the wall oscillates as it crosses the center of the disk.…”
Section: Applicationsmentioning
confidence: 99%
“…Although the switching can be described theoretically by macrospin models [9 and 10], the magnetization reversal caused by STT and SOT is in general a complex and non-uniform process that involves the nucleation and expansion of magnetic domains [11 and 12]. This mechanism prevails over the pure macrospin dynamics even in devices as small as few tens of nm because it is more energetically favorable than the coherent rotation of all the magnetic moments [13][14][15][16]. Time-resolved measurements in magnetic tunnel junctions [16][17][18][19][20] and Hall crosses [21] have revealed that the non-uniform switching comprises two phases at the ns and sub-ns timescale: an initial waiting time t 0 during which the magnetization is at rest and the actual transition of duration ∆t.…”
Section: Introductionmentioning
confidence: 99%